COMPARATIVE ANALYTICAL STUDY OF SAJALA AND NIRJALA NARIKEL LAVANA - Paras D, *Golecha; Siddhisha, Kurve; Ninad, Sathe; Ashish, Punde (International Journal of Ayurveda and Pharma Research, 2016)
Advancement being the heart of development any science, Ayurveda has been no exception to this. Various basic formulations have been mentioned in the classical texts i.e. Samhitas and quite a few were added later on, by contemporary Acharyas. Lavana Kalpana is one of them. Lavana Kalpana literally denotes any pharmaceutical formulation comprising Lavana i.e. any type of salt along with other herbal ingredients. Narikel Lavana has been advised under the Rogadhikara of Parinaam Shula. Acharyas have explained two separate methods of preparation of Narikel Lavana: Sajala (retaining the water inside coconut) and Nirjala (without coconut water). Nirjala Narikel Lavana has been prepared by using Mahaputa and Sajala Narikel Lavana in Kukkutaputa. Current study is aimed at preparation, standardization and comparative study of Narikel Lavana as per two different references with the help of sophisticated analytical technique, XRF. Other methods of examination of Ayurvedic drug formulations such as organoleptic evaluation, physico- chemical tests are also employed. The differences between these values and variations in the XRF analysis have been elaborated here. Organoleptic evaluation of both the samples shows no difference, whereas minor variations are observed in the physico- chemical parameters. XRF analysis has clearly indicated the different between the elemental composition of both Sajal and Nirjala Narikel Lavana.